Deletion of KIBRA, protein expressed in kidney and brain, increases filopodial-like long dendritic spines in neocortical and hippocampal neurons in vivo and in vitro - Blanque, Anja; Repetto, Daniele; Rohlmann, Astrid; Brockhaus, Johannes; Duning, Kerstin; Pavenstädt, Hermann; Wolff, Ilka; Missler, Markus (Frontiers in Neuroanatomy, 2015)
Spines are small protrusions arising from dendrites that receive most excitatory synaptic input in the brain. Dendritic spines represent dynamic structures that undergo activity-dependent adaptations, for example, during synaptic plasticity. Alterations of spine morphology, changes of spine type ratios or density have consequently been found in paradigms of learning and memory, and accompany many neuropsychiatric disorders. Polymorphisms in the gene encoding KIBRA, a protein present in kidney and brain, are linked to memory performance and cognition in humans and mouse models. Deletion of KIBRA impairs long-term synaptic plasticity and postsynaptic receptor recycling but no information is available on the morphology of dendritic spines in null-mutant mice. Here, we directly examine the role of KIBRA in spinous synapses using knockout mice. Since KIBRA is normally highly expressed in neocortex and hippocampus at juvenile age, we analyze synapse morphology in intact tissue and in neuronal cultures from these brain regions. Quantification of different dendritic spine types in Golgi-impregnated sections and in transfected neurons coherently reveal a robust increase of filopodial-like long protrusions in the absence of KIBRA. While distribution of pre- and postsynaptic marker proteins, overall synapse ultrastructure and density of asymmetric contacts were remarkably normal, electron microscopy additionally uncovered less perforated synapses and spinules in knockout neurons. Thus, our results indicate that KIBRA is involved in the maintenance of normal ratios of spinous synapses, and may thus provide a structural correlate of altered cognitive functions when this memory-associated molecule is mutated.